Total Zero Doppler Steering - A New Method for Minimizing the Doppler Centroid - Fiedler, Hauke; Börner, Elke; Mittermayer, Josef; Krieger, Gerhard (IEEE Geoscience and Remote Sensing Letters, 2005)
This letter presents a new method, called total Zero Doppler steering, to perform yaw and pitch steering for space-borne synthetic aperture radar (SAR) systems. The new method reduces the Doppler centroid to theoretically 0 Hz, independent of the range position of interest. Residual errors are only due to pointing inaccuracy or due to approximations in the implementation of the total zero Doppler steering law. This letter compares the new method with currently applied methods. The attitude angles and the residual Doppler centroid frequencies are calculated and depicted exemplarily for the parameters of TerraSAR-X, for which the new method will be implemented and used. The new method provides a number of advantages. The low residual Doppler centroid and the reduced variation of the Doppler centroid over range allow a more accurate Doppler centroid estimation. Due to the low residual Doppler centroid, the synthetic aperture radar (SAR) processing can be alleviated, since the range cell migration is reduced and the Doppler frequencies are low. This facilitates the use of very efficient processing algorithms, which are based on approximations whose quality is better for low Doppler frequencies. The new method will furthermore optimize the overlap of the azimuth spectra of SAR image pairs for cross-track interferometry. Low Doppler centroids will also reduce the impact of coregistration errors on the interferometric phase. Furthermore, scalloping corrections in the ScanSAR processing are alleviated due to the low variation of the Doppler centroid over range. © 2005 IEEE.
DLR Import::2019-04-02
Keywords: Doppler centroid; Synthetic aperture radar (SAR); Yaw steering; Zero Doppler steering